1985
DOI: 10.1002/ccd.1810110502
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cardiomyopathy: Functional status, hemodynamics, arrhythmias, and prognosis

Abstract: The natural history of dilated cardiomyopathy is variable, and the prognosis difficult to predict. Several clinical and hemodynamic parameters have been proposed as prognostic indicators. Reports on the relationship between ventricular arrhythmias, degree of hemodynamic impairment, and sudden death are controversial. To define accurately the prognosis in dilated cardiomyopathy, 55 patients with this clinical syndrome underwent clinical evaluation, radionuclide ventriculography, echocardiography, 12-lead electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Another potential limitation, common to most studies evaluating spontaneous arrhythmias by 24‐hour Holter monitoring, could be the variability of NSVT at different recordings 29 . Therefore, the incidence, length, and rate of NSVT could be underestimated without multiple recordings 30 …”
Section: Limitationsmentioning
confidence: 99%
“…Another potential limitation, common to most studies evaluating spontaneous arrhythmias by 24‐hour Holter monitoring, could be the variability of NSVT at different recordings 29 . Therefore, the incidence, length, and rate of NSVT could be underestimated without multiple recordings 30 …”
Section: Limitationsmentioning
confidence: 99%
“…10 Survival in patients with dilated cardiomyopathy has been related to clinical characteristics, hemodynamics, and ventricular function, 11 whereas the natural history as well as prognostic value of co-existing arrhythmias remain controversial. 12 Costanzo-Nordin et al 13 indicated that the natural history of dilated cardiomyopathy is variable and the prognosis difficult to predict. They proposed several clinical and hemodynamic criteria as prognostic indicators and concluded that the relationship between arrhythmias, degree of hemodynamic impairment, and sudden death is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, over 70% of these patients have non-sustained ventricular tachycardia during ambulatory monitoring. 40 The arrhythmias may be inducible in the electrophysiology laboratory but a correlation between ventricular arrhythmias and sudden death in dilated cardiomyopathy has never been confirmed.4' Decompensated congestive heart failure itself is commonly associated with ventricular arrhythmias.…”
Section: Annicoagulationmentioning
confidence: 99%